A novel 3D Cd(ii) coordination polymer generated via in situ ligand synthesis involving C–O ester bond formation. Issue 1 (2nd January 2019) - Wang, Ji-Jiang; Cao, Zhuang; Wang, Xiao; Tang, Long; Hou, Xiang-Yang; Ju, Ping; Ren, Yi-Xia; Chen, Xiao-Li; Zhang, Yu-Qi
Abstract : A 3D Cd(ii ) coordination polymer comprising ligand molecules not included in the original reaction mixtures but instead formed via in situ ligand synthesis involving a C–O ester bond. Abstract : A novel 3D Cd(ii ) coordination polymer {[Cd(ddpa)(2, 2′-bpy)]·H2 O} n (1) (H2 ddpa = 5, 10-dioxo-5, 10-dihydro-4, 9-dioxapyrene-2, 7-dicarboxylic acid, 2, 2′-bpy = 2, 2′-bipyridine) is hydrothermally synthesized in situ, and the influencing factors and mechanism for the in situ reaction are briefly discussed. The synthesis of1 requires the formation of a new C–O ester bond. This current study confirms that metal ions and N-donor ligands play important roles in the domination of the in situ ligand from 6, 6′-dinitro-2, 2′, 4, 4′-biphenyltetracarboxylic acid (H4 dbta). Furthermore, the structure, thermal stability and photoluminescent property of1 are also investigated.